Laparoscopic radical prostatectomy in patients with high-risk prostate cancer: feasibility and safety$dresults of a multicentric study - Varca, Virginia; Benelli, Andrea; Perri, Davide; Gözen, Ali Serdar; Fiedler, Marcel; de la Taille, Alexandre; Casazza, Giovanni; Salomon, Laurent; Rassweiler, Jens; Gregori, Andrea; Gaboardi, Franco (Journal of endourology, 2018)
Introduction: In Western countries about 25% of prostate cancer (PCa) are high-risk tumors at presentation and its treatment is still a matter of debate among urologists. When a surgical approach is preferred the use of a mininvasive tecnique is still difficult due to the lack of data supporting it in literature. The aim of this study is to evaluate feasibility and safety of laparoscopic radical prostatectomy (LRP) for high-risk PCa.Materials and Methods: The study included 1114 patients with high-risk PCa submitted to LRP between 1998 and 2014. High-risk patients were defined according to D'Amico classification. We collected functional and oncological long-term outcomes and evaluated with univariate and multivariate analyses the role of predictive factors for survival and biochemical recurrence (BR).Results: Mean age at treatment was 62 ± 8 years; mean follow-up was 74 ± 50 months. We obtained an overall survival (OS) of 96.6% at a mean follow-up of 74 months (1076 patients) and a disease-free survival of 66.2% (737 patients). Age (p = 0.0006), pT (p < 0.0001), pN (p = 0.0018), and surgical margins (p = 0.0076) resulted as independent predictors for BR in multivariate analysis. pN (p = 0.0025) and Gs (p = 0.0003) are independent predictors for OS and cancer-specific survival in a univariate analysis; just the Gs results significant in the multivariate model.Conclusions: According to our encouraging data about oncological and functional outcomes we believe that radical prostatectomy represents an effective treatment for patients with high-risk PCa and that laparoscopy is a safe approach offering a mini-invasive alternative to open surgery.
Gesehen am 25.03.2020